-5(p+2)=6-p

Simple and best practice solution for -5(p+2)=6-p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(p+2)=6-p equation:


Simplifying
-5(p + 2) = 6 + -1p

Reorder the terms:
-5(2 + p) = 6 + -1p
(2 * -5 + p * -5) = 6 + -1p
(-10 + -5p) = 6 + -1p

Solving
-10 + -5p = 6 + -1p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add 'p' to each side of the equation.
-10 + -5p + p = 6 + -1p + p

Combine like terms: -5p + p = -4p
-10 + -4p = 6 + -1p + p

Combine like terms: -1p + p = 0
-10 + -4p = 6 + 0
-10 + -4p = 6

Add '10' to each side of the equation.
-10 + 10 + -4p = 6 + 10

Combine like terms: -10 + 10 = 0
0 + -4p = 6 + 10
-4p = 6 + 10

Combine like terms: 6 + 10 = 16
-4p = 16

Divide each side by '-4'.
p = -4

Simplifying
p = -4

See similar equations:

| 2(6w-5)=3(4w-1)-8 | | 9t=4(2t-5) | | 9-2(x-7)=7(x-7) | | 2-5(x+1)=5-3x | | 5(x+1)2+2=22 | | 2(8x-3)=20x-58 | | y=67x-7 | | 2(3x+1)=6-3x | | .50x+5=1x | | 7-3(4-x)=-26 | | 5-2(x+1)=17 | | -2(x+1)=5 | | 3(4y-4)-y=11 | | 6x-12x-5=0 | | 1/9x-5/3=0 | | 12(1/4)-8(3/10) | | 12x-4=3(x+1)-x | | 6x-4y=-20 | | 7÷2(1/5) | | -8*7-7y=56 | | 7x^2+5x-14=34-29x | | cosx=7x | | y=6x^2+6 | | X-8+1=3x | | -8*8-7y=56 | | 2+5x=6*(x-4) | | -8-8-7y=56 | | -8-8-7=56 | | x+y+z=2004 | | 50x+30y=600 | | X(2x-5)(4x+3)=0 | | Z=20x+60y |

Equations solver categories